Growth and characterization of ultra-low damping Co₂₅Fe₇₅ thin films - Swyt, Mitchell, author; Buchanan, Kristen, advisor; Ross, Kate, committee member; Menoni, Carmen, committee member (Colorado State University. Libraries, 2020)
This thesis focuses on the growth and characterization of ultra-low damping Co25Fe75 thin films. Ultra-low damping in a metal is of interest for the design of new spintronic devices because this offers the opportunity to move both electrons and spin waves over appreciable distances. In this work, the effects of seed and capping layers on the damping parameter and magnetization are investigated. A series of thin films were deposited using DC magnetron sputtering. A combination of X-ray reflectometry (XRR), vibrating sample magnetometry (VSM), and ferromagnetic resonance spectroscopy (FMR) were used to determine the film quality, saturation magnetization, and damping parameters of each film. The results show that the Ta seed layers promoted smooth film growth for Co25Fe75, but direct interfaces with Ta or Pt resulting in enhanced damping. Cu spacer layers can be used to disrupt the enhancement but promote rough film growth for the studied sample growth conditions. Damping values in agreement with published results were achieved for two films from the set, with α=0.0064 ± 0.0004 for Ta/Co25Fe75 and α=0.0063 ± 0.0011 for Ta/Cu/Co25Fe75/Cu/Ta.
Keywords: magnetization dynamics; ultra-low damping; magnetometry; Co25Fe75